2009
DOI: 10.1021/bi9009264
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic Intermediate Reveals Staggered pH-Dependent Transitions along the Membrane Insertion Pathway of the Diphtheria Toxin T-Domain

Abstract: The pH-triggered membrane insertion pathway of the T-domain of diphtheria toxin was studied using site-selective fluorescence labeling with subsequent application of several spectroscopic techniques (e.g., fluorescence correlation spectroscopy, FRET, lifetime quenching and kinetic fluorescence). FCS measurements indicate that pH-dependent formation of the membrane-competent form depends only slightly on the amount of anionic lipids in the membrane. The subsequent transbilayer insertion, however, is strongly fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
187
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 53 publications
(199 citation statements)
references
References 53 publications
12
187
0
Order By: Relevance
“…Furthermore, CNTs do not undergo changes in secondary structure in response to low pH alone (Fig. 2), as has been reported for diphtheria toxin (42). Thus, the initial interaction of TeNT with the membrane does not appear to require the formation of a membrane-competent state in solution.…”
Section: Discussionsupporting
confidence: 74%
“…Furthermore, CNTs do not undergo changes in secondary structure in response to low pH alone (Fig. 2), as has been reported for diphtheria toxin (42). Thus, the initial interaction of TeNT with the membrane does not appear to require the formation of a membrane-competent state in solution.…”
Section: Discussionsupporting
confidence: 74%
“…Several authors have reported peptide coil-helix transitions induced by binding to bilayers and the existence of interfacial folded intermediates, mostly using fluorescence approaches (19)(20)(21)(22)(23)(24). Although interesting, the results of molecular dynamics simulations of membrane-associated folding and insertion of various peptides are not definitive (25)(26)(27)(28).…”
Section: Discussionmentioning
confidence: 99%
“…On the right, the hydrophobic core of the T-domain is drawn in the OCS conformation with the three transmembrane helices, TH5, TH8, and TH9, and a dipped hairpin formed by shorter helices TH6 and TH7. This topology is based on a combination of measurements of channel activity in planar bilayers [39,40,43] and is supported by additional spectroscopic evidence in model lipid vesicles ( [30,44] and Kyrychenko et al, Journal of Membrane Biology, in press). The translocation Pathway 2 suggests that OCS is a functionally relevant state, which provides a passageway for translocation of the presumably unfolded catalytic domain to the other side of the bilayer (red circle-before translocation; pink circle-after translocation).…”
Section: Comparing the Two Translocation Pathwaysmentioning
confidence: 74%
“…In pathway 2 (gray arrows), the T-domain first adopts the OCS conformation, which then serves as passageway for the translocation of the C-domain and the T-domain's N-terminal helices. The topology of the T-domain in the OCS, i.e., transmembrane helices TH5 (blue helix), and TH8-TH9 (purple helical hairpin), and interfacial helices TH6 and TH7 (gray helices), is based on conductance measurements on planar bilayers [39,40,43] and supported by spectroscopic data in lipid vesicles [30,44]. Replacement of the C-terminal histidines of the T-domain (H322Q, H323Q, H372Q) are known to strongly reduce formation of channels in planar bilayers by blocking the formation of the OCS conformation [37,38].…”
Section: Spectroscopic Evidence For the Difference In Th5 Topology Inmentioning
confidence: 99%
See 1 more Smart Citation